The Integrated Assembly Line Balancing and Parts Feeding Problem with Ergonomics Considerations. Issue 12 (2016) - Battini, Daria; Calzavara, Martina; Otto, Alena; Sgarbossa, Fabio
Abstract: Assembly Line Balancing Problems (ALBPs) describe a partition of tasks into subsets, each subset forming a station load, to optimize some line efficiency measure under specific task-to-station assignment restrictions. In the literature, the assembly line balancing problem is usually solved separately from the assembly parts feeding problem, which is to determine a supply mode for each part associated with assembly tasks. This leaves significant optimization potential untapped. In this work, we consider the problems jointly and set up the Integrated Assembly Line Balancing and parts Feeding Problem (IALBFP). In the formulated IALBFP, we distinguish between two alternative parts supply modes: direct parts feeding in homogeneous load units (big boxes) and indirect lean parts feeding, where parts are supplied in station kits to each station at the beginning of each cycle after some intermediate handing at the supermarket area. In this way, the indirect parts feeding is fully synchronized with operations at the assembly line. We also incorporate ergonomic aspects by increasing processing times of manual tasks by a time increment to recover from fatigue and energy losses. We formulate a mixed-integer model for IALBP and provide guidelines for the implementation of our integrated planning approach in practice. To our best knowledge, we are the first in the literature to model a lean parts feeding system, which is fully synchronized with assembly line operations. Incorporating ergonomic aspects into IALBFP allows to design a satisfactory assembly system in terms of both ergonomics and productivity and is a further novelty of this work. The implementation of the proposed integrated approach in practice may significantly reduce inventories at the line where space is notoriously scarce, minimize time losses due to unproductive activities and lower fatigue of workers.